1995
DOI: 10.1091/mbc.6.11.1479
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of a signaling pathway in cardiac muscle cells by active mitogen-activated protein kinase kinase.

Abstract: Signaling via the Ras pathway involves sequential activation of Ras, Raf-1, mitogenactivated protein kinase kinase (MKK), and the extracellular signal-regulated (ERK) group of mitogen-activated protein (MAP) kinases. Expression from the c-Fos, atrial natriuretic factor (ANF), and myosin light chain-2 (MLC-2) promoters during phenylephrine-induced cardiac muscle cell hypertrophy requires activation of this pathway. Furthermore, constitutively active Ras or Raf-1 can mimic the action of phenylephrine in inducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 39 publications
3
51
0
4
Order By: Relevance
“…60 Although there is considerable evidence that the ERKs participate in myocyte hypertrophy, 61 it is now apparent that ERKs are not the sole mediators of this response. [62][63][64] Indeed, some investigators believe that they may even be inhibitory. 62,64,65 Because GPCR agonists are now known to activate JNKs and p38-MAPKs, the role(s) of these pathways in hypertrophy is under investigation.…”
Section: Stress-responsive Mapks and Hypertrophy Of The Cardiac Myocytementioning
confidence: 99%
See 1 more Smart Citation
“…60 Although there is considerable evidence that the ERKs participate in myocyte hypertrophy, 61 it is now apparent that ERKs are not the sole mediators of this response. [62][63][64] Indeed, some investigators believe that they may even be inhibitory. 62,64,65 Because GPCR agonists are now known to activate JNKs and p38-MAPKs, the role(s) of these pathways in hypertrophy is under investigation.…”
Section: Stress-responsive Mapks and Hypertrophy Of The Cardiac Myocytementioning
confidence: 99%
“…[62][63][64] Indeed, some investigators believe that they may even be inhibitory. 62,64,65 Because GPCR agonists are now known to activate JNKs and p38-MAPKs, the role(s) of these pathways in hypertrophy is under investigation.…”
Section: Stress-responsive Mapks and Hypertrophy Of The Cardiac Myocytementioning
confidence: 99%
“…Many of the signaling events stimulated by Ang II are mediated by members of the mitogen-activated protein kinase (MAPK) family, including the extracellular signal-regulated kinase (ERK), the p38 and the c-Jun NH2-terminal kinase (JNK) (Thorburn et al, 1995). Among the MAPKs, ERK has been focused on the essential regulators of a hypertrophic response although JNK and p38 were recently studied in regulating cardiac hypertrophy (Sugden, 2001;Maller, 2003;Ptashne Sodium tanshinone IIA sulfonate depresses angiotensin IIinduced cardiomyocyte hypertrophy through MEK/ERK pathway and Gann, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In cultured cardiac myocytes, ERKs are activated by hypertrophic stimuli such as angiotensin II (Ang II) [10], phenylephrine [11,12], endothelin 1 [12][13][14] and PMA [13], as well as cellular stresses such as mechanical stretching [15,16] or osmotic shock [17,18]. Although the role of ERKs in phenylephrineinduced cardiac hypertrophy has been studied by several investigators with different methods, reported roles of ERKs in cardiac hypertrophy vary substantially [19][20][21][22][23]. Furthermore, recent evidence indicates that agonists for the G q -coupled receptor activate not only ERKs but also other members of the MAP kinase family, namely JNK and p38 [17,[24][25][26][27][28], and that these MAP kinases are also important in cardiac hypertrophy [25,26,[29][30][31][32] (reviewed in [5]).…”
Section: Introductionmentioning
confidence: 99%